Comprehensive Inspection on the Experimental Ferritic Stainless Steel by Means of Transmission Electron Microscopy and Neutron Diffraction Techniques - Parikin, Parikin; Dani, Mohammad; Iskandar, Riza; Jahja, Aziz Khan; Insani, Andon; Mayer, Joachim (UI Scholars Hub, 2019)
The field of physical metallurgy is one of the primary beacons that guide alloy developments for multipurpose materials such as the in-core structure materials for pressure vessel components and heat exchangers. The surface microstructure of new ferritic steel with significant local constituent materials was characterized by high resolution powder neutron diffractometer (HRPD) and transmission electron microscope (TEM), combined with the energy dispersive X-ray spectroscopy (EDX). The alloy contains73% Fe, 24% Cr, 2% Si, 0.8% Mn, and 0.1% Ni, in %wt. The charge materials were melted by the casting techniques. The neutron diffractograms obtained shows five dominant diffraction peaks at (110), (200), (211), and (220) reflection planes, which is a typical structure for a body centered tetragonal system. The pattern also included some unidentified peaks which were verified to be Al2O3.54SiO2, Cr23C6, and SiC crystals. A piece of alloy which taken from the middle of the ferritic ingots was also characterized by the HRPD; no unidentified peaks were observed. Results from the scanning transmission electron microscopy (STEM) combined with EDX analyses confirmed the neutron identified phase distributions. Also, oxides and carbides were observed to form mainly close to the surface of the steel. Cracks and pores which probably formed during the preparations were also identified close to the surface. Although the ferritic steel was successfully synthesized and characterized, some unidentified phases and defects could still be found in the produced ingots.